The effect of a training program to develop possession of the ball and its relationship to the results of the matches for soccer players - Mohammed Ali Ibrahim (Mustansiriyah Journal of Sports Science, 2024)
The current study aimed to identify the impact of the training program to develop possession of the ball and its relationship to the results of matches for soccer players. The researcher adopted the experimental approach with two experimental and control groups. The experimental group was Among the players of Diyala Sports Club and the control group from Shahabad Sports Club, the research sample reached (20) players, where the sample used the training program to develop possession of the ball, and the results showed a clear development of the research sample in the post-tests, and the reason for this development is due to the importance of the training program